2002
DOI: 10.1002/1521-4141(200209)32:9<2500::aid-immu2500>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive active p21ras enhances primary T cell responsiveness to Ca2+ signals without interfering with the induction of clonal anergy

Abstract: Chronic engagement of the T cell receptor mediates the induction of T lymphocyte unresponsiveness called clonal anergy. The development of such unresponsiveness has been suggested as one of the mechanisms that regulate peripheral tolerance to self‐antigens and hamper the capacity of tumor antigen‐specific T cells to eliminate cancerous cells. In the attempt to enhance the effector function of CD4+ T lymphocytes and their resistance to clonal anergy induction, we have transduced primary T cells with a retrovira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Additional negative regulation of the IL-2 gene at the promoter level independent of upstream signaling has been shown (52)(53)(54). Such additional blocks in anergic cells were invoked by Crespi et al (22) who showed that ERK activation via expression of a constitutively active mutant of Ras was not sufficient to prevent anti-CD3 antibody-induced anergy. Non-physiological activation of the TCR complex by plate-bound antibodies may also account for the inability of Ras-ERK pathways to overcome antibody-induced anergy.…”
Section: Antibody-induced Anergy Cannot Be Prevented By B-raf Expressmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional negative regulation of the IL-2 gene at the promoter level independent of upstream signaling has been shown (52)(53)(54). Such additional blocks in anergic cells were invoked by Crespi et al (22) who showed that ERK activation via expression of a constitutively active mutant of Ras was not sufficient to prevent anti-CD3 antibody-induced anergy. Non-physiological activation of the TCR complex by plate-bound antibodies may also account for the inability of Ras-ERK pathways to overcome antibody-induced anergy.…”
Section: Antibody-induced Anergy Cannot Be Prevented By B-raf Expressmentioning
confidence: 99%
“…Recent studies examining the role of ERK inhibition in T cell anergy have utilized constitutively active or interfering mutants of upstream activators of ERKs (22) as well as the pharmacological inhibition of the ERK kinase MEK (23). These manipulations result in the activation or inhibition of ERK without mirroring physiological levels of regulation (24 -26).…”
mentioning
confidence: 99%
“…Inhibition of AP-1 via negative regulation of Ras might also be essential for maintenance of the anergic state, since introduction of a constitutive active form of Ras into anergic T cells restores IL-2 production and antigen-induced proliferation [52]. On the other hand, there are reports showing that anergy can be induced in T cells transfected with constitutively active Ras [55,56]. IL-2 has been shown to be crucial for cell-cycle entry but also cell-cycle progression from the G 1 to the S phase has been determined as another checkpoint driving T cells towards activation or anergy.…”
Section: Molecular Establishment Of T Cell Anergymentioning
confidence: 99%
“…It remains unclear, however, whether the MAP kinase cascades are the principal targets of the inhibitory mechanism(s) of anergy, or if this defect is simply a consequence of more upstream inhibition. Indeed, ERK inhibition may be unnecessary for the maintenance of anergy, since primary Tcells retrovirally transduced with constitutively active Ras can still be made anergic using anti-CD3 antibodies [332].…”
Section: The Biochemical Features Of Anergymentioning
confidence: 99%